Can the Poor Influence Policy? Participatory Poverty Assessments in the Developing World, Second Edition - Robb, Caroline M. (Washington, DC: World Bank, 2013)
This book focuses on the World Bank's experience with Participatory Poverty Assessments (PPAs). Some practitioners have argued that a number of World Bank PPAs should not be included because they were extractive, did not influence policy, and were not participatory. However, both good and bad practice PPAs is included in this analysis to facilitate learning from past experiences. Participatory poverty assessments are showing the World Bank and other outside observers of poverty that are not the only poverty experts. Poor people have a long overlooked capacity to contribute to the analysis of poverty-and without their insights to know only part of the reality of poverty, its causes, and the survival strategies of the poor. The objective of a comprehensive poverty analysis, therefore, should be to conduct participatory research and household surveys interactively, so that they enhance each other. If a PPA is conducted after the household survey, the results will explain, challenge, reinforce, or shed new light on household survey data. The results of the household survey can also, of course, explain, challenge, or reinforce the PPA. If the PPA is conducted before the household survey, the PPA results could assist in generating hypotheses, shaping the design of the household survey, and developing survey questions appropriate for the respondents. Ideally, this should be an ongoing process whereby both PPAs and household surveys are conducted periodically and feed into each other. The results of past PPAs indicate that when they are used in conjunction with household surveys, the final assessment is a much fuller analysis of the varying dimensions of poverty, and the policy recommendations are more relevant and informed.